Transcendental Reflections: Literary Preservation of Ethnobiological Heritage and Individualism in Betty Smith’s A Tree Grows in Brooklyn - C. Ganesh; Dr. R. Vithya Prabha; Dr. S. Sudha (The Bioscan, 2025)
Literature is a medium of ideological and philosophical transmissions and rich repository of cultural and scientific knowledge. A Tree Grows in Brooklyn by Betty Smith presents a blend of ideological and traditional medical practices representing both ethnobiological knowledge and experiential knowledge passed down through oral traditions and lived realities. This research aims to bridge literary theme with biological knowledge particularly the traditional and home-based remedies for minor health issues. The protagonist’s and her family’s adherence to these folk practices, despite societal skepticism, serves as a survival mechanism and as an assertion of individual agency, a quiet defiance of collectivist medical authority and a reinforcement of transcendentalist and individualist ideals. This approach proposes a diversified methodology that reconsiders canonical literature as a site for retrieving ethnobiological insight, reinforcing the value of lived science in fiction.